1998
DOI: 10.1007/s004380050757
|View full text |Cite
|
Sign up to set email alerts
|

Towards second-generation STS (sequence-tagged sites) linkage maps in conifers: a genetic map of Norway spruce (Picea abies K.)

Abstract: Genetic linkage maps have been produced for a wide range of organisms during the last decade, thanks to the increasing availability of molecular markers. The use of microsatellites (or Simple Sequence Repeats, SSRs) as genetic markers has led to the construction of "second-generation" genetic maps for humans, mouse and other organisms of major importance. We constructed a second-generation single-tree genetic linkage map of Norway spruce (Picea abies K.) using a panel of 72 haploid megagametophytes with a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 50 publications
(66 reference statements)
3
72
1
Order By: Relevance
“…II) represented between 40% (1957) and 54.3% (2736) of the genome. These results are in good accordance with the 2839 cM of the map previously published by Paglia et al [32]. The probability that a new marker added at the map would be linked to another marker present in the framework map was also estimated.…”
Section: Genetic Mapping and Genome Representativeness Of Marker Sampsupporting
confidence: 81%
See 1 more Smart Citation
“…II) represented between 40% (1957) and 54.3% (2736) of the genome. These results are in good accordance with the 2839 cM of the map previously published by Paglia et al [32]. The probability that a new marker added at the map would be linked to another marker present in the framework map was also estimated.…”
Section: Genetic Mapping and Genome Representativeness Of Marker Sampsupporting
confidence: 81%
“…Furthermore, no marker was significantly distorted using a Bonferroni correction. In our study, we revealed a lower or similar level of genetic distortion compared to those reported in other P. abies genome studies (without Bonferroni corrections) where segregation distortion affected 5.6% [32] to 6.6% [1] of markers. Additionally, when loci inheritance was directly compared between the two maternal environments, we detected differences for 1.3% (2735) to 5.7% (1957) of loci per parent at P < 0.05 (Tab.…”
Section: Segregation Analyses and Selectionmentioning
confidence: 47%
“…In spite of its large genome size, the use of appropriate PECs allowed the production of easy-to-score AFLP gels. The use of Pst-Mse PECs has been reported to provide less complex gel patterns but also yields non-randomly distributed markers in conifers [43]. PstI is sensitive to methylation and the use of this endonuclease may target low-copy clustered regions.…”
Section: Aflp Markersmentioning
confidence: 99%
“…Alternatively, other research groups started to use codominant markers such as RFLPs [10,19,54], PCR-RFLP [26], ESTs (Expressed Sequence Tags) [12,47,61] and more recently SSRs (Simple Sequence Repeats) [19,22,43], allowing gene action to be precisely defined (estimation of additive and dominant effects of QTLs, [55]) and providing anchor points in comparative mapping experiments [39].…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites have become the marker system of choice due to their high reproducibility, abundance in genome, hypervariability, and co-dominance. Due to their hypervariability and efficiency in polymorphism detection, SSR markers have become ideal for genetic map construction (Devey et al, 1996;Paglia et al, 1998), identification of clones (Dayanandan et al, 1998), identification of species and hybrids, determination of paternity (van de Ven and McNicol, 1996), and marker-assisted selection (Weising et al, 1997).…”
Section: Introductionmentioning
confidence: 99%